The use of Trichoderma species for the biocontrol of postharvest fungal decay in fruits and vegetables: Challenges and opportunities - Li, Xiaojiao; Liao, Qinhong; Zeng, Shixian; Wang, Yong; Liu, Jia (Postharvest biology and technology, 2025)
Ensuring the stability of the global supply of fruits and vegetables and maintaining the quality and nutritional value of fruits and vegetables during storage and marketing are critical problems that need to be continually addressed. However, postharvest losses due to decay and senescence pose a major threat to the supply of high-quality fruits and vegetables. In fact, postharvest losses caused by decay pathogens can account for 20–25 % of postharvest losses. In recent years, new methods to control postharvest diseases of fruits and vegetables have been explored that are considered safer and more ecofriendly than the use of synthetic, chemical fungicides. In this regard, the use of Trichoderma species as biocontrol agents of both preharvest and postharvest diseases has been the subject of considerable research. Their use for the prevention of postharvest diseases is especially noteworthy as Trichoderma has been shown to be non-toxic and non-harmful to humans and the environment. In this review we provide an overview of the advances that have been made in the use of Trichoderma isolates for controlling postharvest diseases of fruits and vegetables. The review provides information on the identification of Trichoderma species with biocontrol potential, their mode of action, and the challenges and opportunities that exist for the commercial application of Trichoderma in the postharvest environment. Future research topics that need to be addressed on the use of Trichoderma are also presented. •Postharvest fungal decay causes significant loss in fruits and vegetables.•Biocontrol using Trichoderma is promising to manage postharvest decay.•Species, distribution, and properties of Trichoderma are introduced.•Mechanisms of action involved in the postharvest biocontrol system are reviewed.•Challenges and prospects of commercial Trichoderma products are discussed.